Gaya Bahasa Amtsal dalam Al-Qur’an: Studi Perumpamaan untuk Penyampaian Nilai Moral dan Spiritual - Sholehah, Nurhilaliah Fitri; Sanah, Siti; Nailurrahmi, Fitma; Fauziyatullah, Hilma Auliya (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2024)
The Qur'an uses various styles of language to convey moral and spiritual messages, one of which is uslub al-amtsal (the style of parables). Although it plays an important role, in-depth studies on how this linguistic style simplifies abstract concepts and reinforces the messages of the Qur'an have received limited attention. Understanding this is crucial so that the messages in the Qur'an can be more easily accessed and remain relevant to contemporary readers. This study aims to answer the question: How do the parables in the Qur'an explain abstract concepts and strengthen the messages conveyed? Using a descriptive-analytical qualitative approach, this research analyzes verses containing amtsal, utilizing primary data from books on the language style of the Qur'an, as well as secondary data from journal articles and relevant books. The findings reveal that uslub al-amtsal functions to simplify, clarify, and reinforce the meanings of the teachings conveyed. Thus, this study contributes to understanding how the Qur'an utilizes language styles as an effective communication tool to deliver moral and spiritual messages.